PROBLEMATIKA CARA MEMAHAMI HADIS AKHIR ZAMAN DALAM PANDANGAN AHL AL-SUNNAH WA AL-JAMĀ’AH - Misbahuddin Misbahuddin (Ushuluna: Jurnal Ilmu Ushuluddin, 2018)
The end-time traditions differ slightly from other traditions because they are predictive and cannot be ascertained when they occur. Themes related to end-time hadiths such as the appearance of al-Mahdi, the Antichrist, Jesus, and the Great War seized many Muslim scholars to interpret them. Sometimes, certain interpretations have tendencies that are biased. There are a lot of debates related to these traditions, for example, are the traditions of ahad and israiliyyat about the end of time accepted? Sunni clerics choose to use ahad and be careful in responding to israiliyyat. They also offer several stages in formulating it.